Assessing the Influence of Education Efficiency in the European Union. - Mamatzakis, Emmanuel C. (Kyklos, 2025)
This study aims to evaluate the efficiency of education in the EU using an optimisation approach based on a directional distance function and stochastic nonparametric data envelopment analysis. In the second stage, it explores how GDP per capita responds to education efficiency through a panel VAR model. The results show that education efficiency is lower than previously reported in the literature but remains higher than the efficiency of general government expenditure. On average, the EU's education efficiency score is 0.6, indicating a notable inefficiency of 0.4. Increasing government spending and lowering student‐to‐teacher ratios across EU countries could enhance education efficiency. Furthermore, the response of GDP per capita to improvements in education efficiency is positive. These findings have important policy implications under the new EU economic governance framework, suggesting that EU countries should prioritise education spending within the scope of the new multi‐year government expenditure targets.